Unequal Behaviour between Hydrolysable Functions of Nirmatrelvir under Stress Conditions: Structural and Theoretical Approaches in Support of Preformulation Studies - Philippe-Henri Secretan; Maxime Annereau; Willy Kini-Matondo; Bastien Prost; Jade Prudhomme; Lina Bournane; Muriel Paul; Najet Yagoubi; Hassane Sadou-Yayé; Bernard Do (Pharmaceutics, 2022)
Nirmatrelvir is an antiviral drug approved for the treatment of COVID-19. The available dosage form consists of tablets marketed under the brand name PAXLOVID®. Although knowledge of nirmatrelvir’s intrinsic stability may be useful for any potential development of other pharmaceutical forms, no data regarding this matter is available to date. Preliminary forced degradation studies have shown that the molecule is stable under oxidative and photolytic conditions, while hydrolytic conditions, both acidic and basic, have proven deleterious. Indeed, the molecule presents a priori several functions that can undergo hydrolysis, i.e., three amide moieties and a nitrile function. However, considering the degradation products formed under forced conditions and which were detected and identified by LC-UV-HRMSn, the hydrolysis process leading to their formation is selective since it involved only 2 of the 4 hydrolysable functions of the molecule. Ab initio studies based on density functional theory (DFT) have helped better understand these reactivity differences in aqueous media. Some hydrolyzable functions of nirmatrelvir differ from others in terms of electrostatic potential and Fukui functions, and this seems to correlate with the forced degradation outcomes.